Unraveling the Dynamics Between Advanced Technology, Logistics Customer Service, and Logistics Performance to Boost Customer Retention: Evidence from Shopee Express - Muhamad Faisal Nasrudin; Agus Purnomo; Melia Eka Lestiani (Journal of Consumer Sciences, 2025)
Background: